مدى توافق مهنة التدقيق في سورية مع المعايير المهنية لرقابة الجودة دراسة تحليلية - دحدوح حسين; الشاهين عصام تركي (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يستهدف هذا البحث دراسة مدى تطبيق مهنة تدقيق الحسابات في سورية للمعيار الأول من معايير التدقيق الدولية وكذلك المعيار 220 المعنيان بجودة التدقيق. وقد استهل البحث ببيان أهمية ضبط الجودة ومستوى التركيز الدولي على رفع مستوى جودة التدقيق وذلك من خلال التقيد بتطبيق المعايير المهنية التي نوهت إلى مرونة التطبيق ومراعاة ظروف الحال، ولا يقل عن ذلك أهمية تطبيق مقتضيات القوانين والأنظمة ومراعاة رغبات المستثمرين. وقد عمد الباحث إلى تصميم استبانة تتألف من 23 سؤالاً وزعت على عينة تتألف من مئة محاسب قانوني من مدققي الشركات وقد تم التوزيع عن طريق جمعية المحاسبين القانونيين في سورية وقد شملت العينة مجلس إدارة الجمعية واللجان التابعة للجمعية في مدينة دمشق وريفها، وقد تلقى الباحث 38 رداً تم تصنيفها واختبارها إحصائياً، حيث دلت الإختبارات الإحصائية على إمكان الثقة بنتائج الإختبار واعتباره ممثلاً لمدققي الحسابات السوريين. وقد دلت نتائج العينة على أن المهنة في سورية تمارس مستوى خجولاً من الرقابة على الجودة، ويعود السبب في ذلك إلى عدم انتشار ثقافة الجودة في أوساط المهنة وخلال العاملين في منشآت أو مكاتب التدقيق. ومن أهم عوامل تدني تطبيق معايير الجودة هو ضعف الاستقلال الذي يمثل العمود الفقري للجودة وقد بدا ذلك من خلال مجموعة مؤشرات أهمها:غياب صندوق الشكاوى داخل منشأة أو مكتب التدقيق، وعدم الاطمئنان على تمتع العاملين في منشأة التدقيق بالاستقلال بشكل دوري. كما دلت النتائج على ضعف مستوى تطبيق القوانين والأنظمة النافذة وخاصة قاعدة الأربع سنوات وقاعدة الأربع شركات. وأخيراً دلت النتائج على عدم مراعاة المهنة في سورية لرغبات المستثمرين وحاجاتهم المتغيرة. This research intends to study the implementation of the ISA 1 and ISA 220 relating to quality control by the Syrian audit profession. The paper starts by assessing the importance of quality control in auditing and the international lobbying to raise the level of quality control in the auditing profession through the application of audit standards which state that flexibility and keeping all relevant circumstances in mind are necessary. To obtain realistic results, a questionnaire of 23 questions has been distributed to a sample of 100 Syrian chartered accountants working in the field of companies’ audit. The distribution of questionnaire has been carried out by the Syrian Association of Chartered Accountants. The researcher has received 38 valid replies which have been systematically classified and tested by SPSS package. The results revealing and can be considered representative of Syrian chartered accountants. The results reveal that the Syrian performance of chartered accountants falls way short of any credible implementation of quality control. Basically, this can be due to the absence of quality control "culture", on the one hand, and the lack of independence, on the other. This is despite the fact that these two factors (quality control "culture" and the lack of independence) are considered, by many, the cornerstone of the quality control doctrine. In so many auditing firms, it was clear that there were no communication channels between dissatisfied employees and the administration. Furthermore, the level of human resources was less than satisfactory. The results indicated that the auditing profession in Syria is not compatible with the laws and regulations of auditing, namely: the 4years rule and 4 companies rule. Moreover, auditors do not stand up to the level of satisfaction the investors are looking for.